Bacterial community of marine sponges from Pulau Bidong and Pulau Karah, Terengganu and the haloacid degrading potential - Wan Syafiqa Meor Hissan (Kulliyyah of Science, International Islamic University Malaysia, 2019)
The industrial progression marks a massive transition in manufacturing and agricultural fields. Such revolution encounters accumulation of xenobiotic compounds due to the widespread use of herbicides and pesticides hence contributing to the environmental pollution. As far as one can tell, microbial dehalogenase is believed to remove halogenic ions and convert it into harmless chemical form. The crucial step for this conversion is the cleavage of carbon-halogen bond; dehalogenation. Dehalogenase gene can be isolated from different sources. The most common source of isolation is from soil contaminated area but very little is known from marine environment. Thus, in this study we aim to screen dehalogenase gene from haloacid degrading bacteria associated with marine sponges and compare it with their total bacteria population. Marine sponge which harbours an extensive microbial diversity has made it a potent and excellent candidate for the haloacid degrading bacteria isolation. Therefore, the diversity and difference in bacterial as well as archaea communities between two different sponges using 16S rRNA amplicon sequencing were assessed. Phylum Proteobacteria (41.40%) and Crenarchaeota (49.1%) were reported dominating sponge E while phylum Chloroflexi has 47.50% which made up nearly half of the total bacteria population of sponge C. Sponge suspension was spread on minimal media supplemented with 2,2-dichlropropanoic acid as their sole carbon in an attempt to culture for the culturable bacteria and compare them with the total bacteria population from Illumina Hiseq DNA sequencing platform. Bacillus sp. was successfully isolated from sponge C and all strains were tested with primer DHAR 1000 F/DHAR 1350 R to screen for the dehalogenase gene. However, adenosine deaminase (ADA) gene was obtained suggesting that halorespiration was also mediated by ADA in this case. Bacillus sp. represents a minority community in sponge C (0.02%) demonstrating that potential haloacid degrading bacteria could be isolated even in a well-preserved area despite their small population provided that they possess the mechanism to degrade halogen. Nevertheless, these findings showed it is possible to isolate haloacid degrading bacteria from sponges that can be further utilized for bioremediation of contaminated environment